Simulation in Neonatal-Perinatal Medicine Fellowship Programs - Sawyer, Taylor; Stavroudis, Theodora A.; Ades, Anne; Dadiz, Rita; Dammann, Christiane E. L.; Halamek, Louis P.; Moussa, Ahmed; Soghier, Lamia; Gupta, Arika; Aliaga, Sofia; Umoren, Rachel; French, Heather; for the Organization of Neonatal-Perinatal Training Program Directors Task Force on Simulation (American Journal of Perinatology, 2019)
Objective This study aimed to investigate the use of simulation in neonatal-perinatal medicine (NPM) fellowship programs.Study Design This was a cross-sectional survey of program directors (PDs) and simulation educators in Accreditation Council for Graduate Medical Education (ACGME) accredited NPM fellowship programs.Results Responses were received from 59 PDs and 52 simulation educators, representing 60% of accredited programs. Of responding programs, 97% used simulation, which most commonly included neonatal resuscitation (94%) and procedural skills (94%) training. The time and scope of simulation use varied significantly. The majority of fellows (51%) received ≤20 hours of simulation during training. The majority of PDs (63%) wanted fellows to receive >20 hours of simulation. Barriers to simulation included lack of faculty time, experience, funding, and curriculum.Conclusion While the majority of fellowship programs use simulation, the time and scope of fellow exposure to simulation experiences are limited. The creation of a standardized simulation curriculum may address identified barriers to simulation.
Keywords: simulation; neonatal-perinatal medicine fellowship; neonatology; fellowship; medical education